For Country and Honor Through Blood and Anguish: The Life and Trials of the Soldiers of the 3rd Wisconsin Infantry Regiment - Rase, Lucas D. (My University, 2011)
War is not always glorious. Family, friends, and fellow soldiers are wounded and killed fighting for a cause and expect nothing in return except for respect, freedom and a peaceful life. The American Civil War divided a nation into two and had fathers, husbands, brothers and sons fight their fellow countrymen, and even their family divided by politics in order to attain the ultimate goal of victory. The soldier led three aspects of life: a military life (defined by drills and battles), a life outside of battle and drills, and their home life (which was maintained through the post). The Third Wisconsin Volunteer Regiment exhibited these aspects clearly through their letters and through their memoirs. Through their eyes, we can feel what it was like to fight in the bloodiest war in American history. Through their eyes, we will learn more about the everyday life of a soldier. Through their eyes, we will expand our knowledge of the Civil War in a manner different from many textbooks in school.
Keywords: United States--History--Civil War, 1861-1865--Regimental histories--Wisconsin; United States--History--Civil War, 1861-1865--Personal narratives; United States. Army. Wisconsin Infantry Regiment, 3rd (1861-1865)